Aging and functionality of the institutionalized elderly people of Alto Alentejo: Contributions to the diagnosis of the situation - Arco, Helena (2022)
The loss of functionality in aging process is a concern nowadays. We proposed to perform the diagnosis of the functionality of institutionalized elderly people in Portalegre city. We developed a quantitative, descriptive and transversal study with the application of three evaluation instruments (Elderly Nursing Core Set, Mini-Mental State Examination and Blessed Dementia Scale (BDS)). The sample consisted of 89 elderly people, with an average age of 86.6 years-old, most of them are female (71.9%), widowed (77,5%) and illiterate (51.7%). The average of years of institutionalization was 3.5. 45.3% showed cognitive deterioration, and 50% showed moderate to severe deficits on the BDS. It was also found that 7% of the older people had low weight and 79.4% were overweight. It was also found that 7% of them had low weight and 79.4% were overweight. 37% reported they have pain and more than 52% presented moderate to complete disability in daily life activities such as walking, washing, caring for body parts, excretion processes and dressing. However, less than 26% presented some deficiency in eating. Regarding environmental factors 88% of the elderly people reported having some kind of support from family and friends. We concluded that the sample presents functional deficits, including considered cognitive deficiencies, requiring intervention. Considering that the evaluation presented here was made before the pandemic period caused by Covid-19, it is important to re-evaluate this sample after the restrictions of social conviviality to assess the effect of the pandemic on functionality and rethink the model of care for the institutionalized elderly people.